Communities on the margin: disadvantaged populations in Indian society - Ḥasanain, Nadīm (Routledge, Taylor & Francis Group, 2024)
"This book probes into the marginalized communities of the Indian society through historical and contemporary societal perspectives. It discusses socio-cultural aspects of the experiences of Scheduled Castes, Dalits, Scheduled Tribes/tribal communities, Other Backward Classes, linguistic minorities, religious minorities and the queer/LGBT as sexual minorities. Adopting an inter-disciplinary approach, it looks at all these segments of Indian society through historical and societal perspectives. Divided into three broad sections - Scheduled Castes, Scheduled Tribes, and minorities, this book provides historical perspective backed by the contemporary situation and emerging social changes among these communities. Written in a lucid manner, the book aims to reach and impact readers without having any prior academic exposure to this subject area. This book would be useful to the students, researchers and teachers of sociology, social work, history, economics, political science, and other interdisciplinary courses in social sciences. The book will also be valuable reading for those interested in South Asian studies, especially contemporary Indian society"--